Treatment of Chronic Hepatitis B with Interferon: Long Term Follow-Up - Jean-Pierre Villeneuve; Bernard Willems (Canadian Journal of Gastroenterology)
The aim of treatment of chronic hepatitis B with interferon is to induce a transition from the replicative phase of the disease to a nonreplicative state, with loss of hepatitis B virus (HBV)-DNA, seroconversion from hepatitis B e antigen (HBeAg)-positive to anti-HBe antibody-positive, and normalization of liver enzymes. The authors’ experience in 22 patients with chronic hepatitis B treated with recombinant human interferon alpha-2b (5 MU/m2 subcutaneously three times/week for 16 weeks) is reported. Before treatment all patients had been positive for hepatitis B surface antigen (HBsAg) and HBeAg for at least six months, had abnormal serum aminotransferases, had no evidence of hepatitis D or human immunodeficiency virus (HIV) infection and had compensated liver disease. Eleven of 22 patients (50%) responded to treatment with loss of HBeAg and appearance of anti-HBe antibodies, and normalization of serum aminotransferases within six months of interferon cessation. Patients were followed for 3.4±1.2 years after treatment. Ten of 11 responders remained negative for HBeAg and HBV-DNA; one patient relapsed and responded to a second course of interferon with loss of HBeAg and HBV-DNA. Seven of the 11 nonresponders underwent spontaneous (n=5) or retreatment-induced (n=2) seroconversion from HBeAg to anti-HBe and loss of HBV-DNA during follow-up. The other four nonresponders remained positive for HBeAg and HBV-DNA; three of the four progressed to decompensated liver disease. It is concluded that interferon is an effective treatment of chronic hepatitis B in 50% of patients with features similar to those used as selection criteria in the present study. These criteria probably also identify patients who have a high likelihood of spontaneous HBeAg to anti-HBe seroconversion, and it is possible that the benefit of interferon is its acceleration of this seroconversion.